A historical Southern Ocean climate dataset from whaling ships' logbooks. (2nd March 2019) - Teleti, Praveen R.; Rees, W. G.; Dowdeswell, Julian A.; Wilkinson, Clive
Abstract: Historical ship logbooks provide vital historic meteorological observations in the Southern Ocean, one of the largest climate‐data deficient regions on the Earth. Christian Salvesen Whaling Company logbooks from whaling ships operating in the Southern Ocean, starting from the 1930s through the 1950s, are examined. Meteorological information contained in these logbooks has been extracted to produce a historical climate dataset. We discuss various instructions recommended by the British Admiralty to observe and record weather conditions on‐board whaling ships. Statistical tests were used to flag erroneous values and corrections were made using neighbouring values. Meteorological parameters such as air pressure, air and sea temperature and wind force on the Beaufort scale were standardized, converting imperial to metric units. The data were structured according to the internationally accepted International Maritime Meteorological Archive format, which includes the most commonly reported meteorological variables, including the time, location and ship‐related meta‐data. Hence, a readily accessible, error‐corrected and standardized historical climate dataset of the Weddell Sea sector of the Southern Ocean is presented. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://doi.org/10.17863/CAM.31530 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .